Stress distributions in maxillary central incisors restored with different high-stiffness post models: 3-D FEA - Srayeddin, Bassam; Almuntashri, Ali (International Journal of Dental Research, 2018)
Background: Dental root posts are recommended for endodontically treated weakened teeth.Objectives: The present computational FEA study aims to evaluate the effect of material and design of the post on the stress distribution under load in different root canal shapes of endodontically treated maxillary central incisor (MCI).Methods: Three-dimensional models of (MCI) were created by using CAD modeling software and divided into two groups. Group-I comprised five models of a weakened root restored using different post materials (stainless steel, titanium, gold-alloy, Ni-Cr, and zirconium). Group-II: involved four models of (MCI) with two different root canal shapes (small and wide) restored using cylindrical (C-Post) and two-stage tapered (T-Post) posts. Each tooth model was subjected to a 100 N oblique load at the palatal surface of the crown. Von Mises equivalent stresses on dentin and post, as well as shear stresses on the post cement, were evaluated.Results: In Group-I: Ni-Cr produced the lowest stress values on the dentin, where titanium and gold-alloy posts produced the lowest stresses in the post and post/root interfaces. In Group-II: Roots restored with a T-Post showed a lower concentration stress in the dentin and lower shear stresses in the cement layer compared with those restored with a C-Post.Conclusion: The geometry of the post and the corresponding material play an important role in the stress behavior of restored teeth. The use of titanium or gold-alloy T-Posts seems a good way to improve the stress distribution profile and reduce the risk of restoration failure.Â Â Â